Effect of Osteotomy Preparation on Osseointegration of Immediately Loaded, Tapered Dental Implants. (March 2016) - Stavropoulos, A.; Cochran, D.; Obrecht, M.; Pippenger, B.E.; Dard, M.
The aim of the present preclinical in vivo study was to evaluate whether a modified "drill-only" protocol, involving slight underpreparation of the implant site, may have an effect on aspects of osseointegration of a novel bone-level tapered implant, compared with the "standard drilling" protocol involving taping and profiling of the marginal aspect of the implant socket. In each side of the edentulated and completely healed mandible of 11 minipigs, 2 tapered implants (8 mm long × 4.1 mm Ø, BLT; Institut Straumann AG, Basel, Switzerland) were installed either with the drill-only or the standard drilling protocol. Significantly lower average insertion torque values were recorded for the standard drilling protocol group (52 ± 29 Ncm) compared with the drill-only group (70 ± 27 Ncm) ( t test, P ≤ 0.05); no significant difference was observed between the 2 groups regarding implant stability, by means of resonance frequency analysis (75 ± 8 vs. 75 ± 6, respectively). Half of the implants were immediately loaded and the rest were submerged, providing observation times of 8 or 4 wk, respectively. Non-decalcified histological and histomorphometric analysis of the implants with surrounding tissues showed no significant differences between the 2 drilling protocols regarding the distance from the implant platform to the first coronal bone-to-implant contact (f-BIC), the total bone-to-implant contact (BIC) as a percentage of the total implant perimeter, and the bone density in an area extending 1 mm laterally from the implant (BATA) within 2 rectangular regions of interest (ROIs) 4 mm in height, representing the coronal (parallel-walled) and apical (tapered) aspect of the implant (ROI 1 and ROI 2, respectively) in non-submerged implants. In general, marginal peri-implant bone levels were at or slightly apical to the implant platform, and large amounts of bone-to-implant contact were observed. In contrast, immediately loaded implants placed with the drill-only protocol showed statistically significantly lower BIC values (66% ± 13.7%) compared with those installed with the standard drilling protocol (74.8% ± 11.2%) ( P = 0.018). In addition, although marginal bone levels were in most of the immediately loaded implants at or slightly apical to the implant platform, some of the implants installed with the drill-only protocol showed marginal bone loss and crater formation. Thus, in this model system, even slight underpreparation of the implant socket appeared to compromise osseointegration of immediately loaded bone-level tapered implants.